2020
DOI: 10.1101/2020.02.18.952978
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synaptomic analysis of dopaminergic inputs reveal hub synapses in the mouse striatum

Abstract: Highlights:1. Fluorescence Activated Synaptosome Sorting allows for the establishment of a molecular synaptome of striatal dopaminergic projections. 2. Dopaminergic varicosities adhere to receptor filled post-synaptic membranes. 3. Dopaminergic projections build hub synapses with excitatory and inhibitory projections. 4. SynCAM 2 is a strong candidate for the adhesion and differentiation of dopamineeffector hub synapses. SUMMARYDopamine transmission is a monoaminergic system involved in reward processing and m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 98 publications
(202 reference statements)
0
10
0
Order By: Relevance
“…One possibility is that NL‐2 plays a role in the establishment of GABA release sites by DA neurons 10,51 . The implication of other cell adhesion molecules such as SynCAM2 also needs to be examined as recent work has also revealed the presence of this protein in striatal synaptosomes containing DAergic terminals linked to postsynaptic domains 82 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that NL‐2 plays a role in the establishment of GABA release sites by DA neurons 10,51 . The implication of other cell adhesion molecules such as SynCAM2 also needs to be examined as recent work has also revealed the presence of this protein in striatal synaptosomes containing DAergic terminals linked to postsynaptic domains 82 …”
Section: Discussionmentioning
confidence: 99%
“…10,51 The implication of other cell adhesion molecules such as SynCAM2 also needs to be examined as recent work has also revealed the presence of this protein in striatal synaptosomes containing DAergic terminals linked to postsynaptic domains. 82 In the context of the strong ability of NL-1 to promote synapse formation by DA neurons, a limited formation of synapses by DA neurons in vitro and in vivo could perhaps be due to limited levels of Nrxn-1 at individual terminals. Although we found that Nrxn-1α and Nrxn-1ß are robustly expressed by DA neurons, the fact that DA neurons in rodents are thought to establish upwards of 100 000 individual release sites along their axonal arbor 15 could give rise to limited levels of presynaptic transsynaptic proteins in these terminals.…”
Section: Presynaptic Nrxn-1α Ss4− and Postsynaptic Nl-1 Ab Influence Synapse Formation By Da Neuronsmentioning
confidence: 99%
“…Dissecting the molecular composition of specific connections remains a major challenge. Sorting of growth cones 69 and specific synapse types (Pfeffer et al 70 , this study), imaging-based approaches [71][72][73] , affinity purification 74 , and proximity biotinylation [75][76][77] each have their advantages and disadvantages 78 . Here, we combined biochemical enrichment, antibody labeling of a synapse type-enriched surface marker, and fluorescent sorting to isolate MF synapses.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect this is due to the high density of boutons en passant along dopaminergic axons, which would provide a strong representation of the entire axonal proteome upon resealing as synaptosomes. Our data thus highlight the utility of the synaptosome sorting technique developed by Herzog and colleagues as a complementary approach for study of the presynaptic proteome (Biesemann et al, 2014;Pfeffer et al, 2020). Future work will determine whether the strong correlation between axonal and synaptosomal proteomes is a unique feature of DA neurons.…”
Section: Discussionmentioning
confidence: 66%